DTMF BASED CONTROLLED ROBOT VEHICLE - Sasidhar, Sirigereddy; Nagamani, Arekallu; Prashanthi, K T; Farzana, Shaik (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
In this paper, we can control the Robot using Dual Tone Multi Frequency (DTMF) technology. DTMF technology is most useful technique at present days. It is worked on to methods digital signal processing (DSP). Wireless-control of robots uses RF circuit that has the drawbacks of limited working range and limited control. This DTMF is gives advantage over the RF; it increases the range of working and also gives good results in case of motion and direction of robot using mobile phone through micro controller. This type of wireless communication gives the remote handling operation of Robot using DTMF.